2010
DOI: 10.1182/blood-2009-04-215756
|View full text |Cite
|
Sign up to set email alerts
|

The small 11kDa nonstructural protein of human parvovirus B19 plays a key role in inducing apoptosis during B19 virus infection of primary erythroid progenitor cells

Abstract: Human parvovirus B19 (B19V) infection shows a strong erythroid tropism and drastically destroys erythroid progenitor cells, thus leading to most of the disease outcomes associated with B19V infection. In this study, we systematically examined the 3 B19V nonstructural proteins, 7.5kDa, 11kDa, and NS1, for their function in inducing apoptosis in transfection of primary ex vivo-expanded erythroid progenitor cells, in comparison with apoptosis induced during B19V infection. Our results show that 11kDa is a more si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(82 citation statements)
references
References 46 publications
3
77
1
1
Order By: Relevance
“…Similarly, the newly identified splice acceptor site at AAV2 nt 4138 may have counterparts in B19 (nt 4883) and SPV (nt 4638) at the right ends of the respective genomes. For parvovirus B19, a multiply spliced transcript involving the above-described splice sites is translated to a small protein of 11 kDa, which appears to increase viral infectivity in vivo (52) and may play a role in apoptosis and cell signaling pathways (53,54). In cell culture the novel 18-kDa Rep/VP protein only had a minor effect on AAV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the newly identified splice acceptor site at AAV2 nt 4138 may have counterparts in B19 (nt 4883) and SPV (nt 4638) at the right ends of the respective genomes. For parvovirus B19, a multiply spliced transcript involving the above-described splice sites is translated to a small protein of 11 kDa, which appears to increase viral infectivity in vivo (52) and may play a role in apoptosis and cell signaling pathways (53,54). In cell culture the novel 18-kDa Rep/VP protein only had a minor effect on AAV replication.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking the expression of the 11-kDa protein in recombinant virions significantly reduces viral infectivity; the expression of the small protein could be critical for VP2 protein expression and trafficking in infected cells (102). Chen and colleagues showed recently that the 11-kDa protein was highly expressed (at least 100 times more than NS1) in erythroid progenitors, mostly in the cytoplasm, and was a major inducer of apoptosis by the activation of caspase 10 (an initiator caspase recruited at the top of the caspase signaling cascade in the death receptor signaling pathway) (14). Moreover, B19V DNA could activate Toll-like receptor 9 into erythroid cells, leading to inhibition of cell growth (34).…”
Section: Virus Replication and Cell Apoptosismentioning
confidence: 99%
“…The 7.5-kDa and 11-kDa proteins encoded by abundant small mRNAs of B19V are unique among the parvoviruses characterized to date. Recently, Chen et al reported that the 11-kDa protein is a significant inducer of apoptosis in erythroid progenitors (14). NS1 is cytotoxic and plays a crucial role in B19V pathogenesis.…”
Section: Introductionmentioning
confidence: 99%